Gender, Faith, and Reform: A Narrative Review of Islamic Feminism and Public Policy - Rofiq, Nur (Sinergi International Journal of Islamic Studies, 2024)
The discourse on gender in Islam has gained increasing scholarly attention due to its profound implications for justice, human rights, and societal development in Muslim-majority contexts. This study aims to examine how Islamic thought has addressed gender through various interpretative approaches and the role of legal, institutional, and political systems in shaping these discourses. Using a narrative review methodology, literature was systematically sourced from major academic databases including JSTOR, Scopus, and Google Scholar. Keywords such as "gender and Islam," "Islamic feminism," and "tafsir and gender" guided the selection of peer-reviewed articles and critical texts. The review reveals a fundamental divide between textualist interpretations that reinforce patriarchal norms and contextualist approaches advocating gender justice. Feminist scholars such as Amina Wadud and Ziba Mir-Hosseini have significantly influenced the reinterpretation of sacred texts, promoting inclusive theological frameworks. Institutions and clerics play dual roles as both agents of change and conservators of tradition, with education emerging as a transformative force. Case studies from Indonesia, Iran, and Morocco illustrate how national legal and political environments mediate the implementation of gender policies. Progressive reforms in Indonesia contrast with the restrictive policies in Iran and gradual reform efforts in Morocco. Findings emphasize the need for gender-sensitive education, inclusive fatwas, and political participation as strategic pathways toward gender justice. The study concludes that collaborative, interdisciplinary, and context-sensitive approaches are essential for transforming gender discourse in Islam and informing inclusive public policy.